PERFORMANCE APPRAISAL OF PMFBY VIS-À-VIS RWBCIS IN INDIA - S.M. KEERTHI KUMARA and D. SUJATHA SUSANNA KUMARI, (The Journal of Research ANGRAU, 2020)
The study aimed to overview the numerous crop insurance schemes in India from its initial schemes tothe present schemes. The study appraised the performance of “Pradhan Mantri Fasal Bhima Yojana” (PMFBY)vis-a-vis “Restructured Weather Based Crop Insurance Scheme” (RWBCIS) from 2016-17 to 2018-19.Thegrowth rate analysis calculated to examine the number of farmers covered and the total agriculture areainsured under the schemes indicated that the number of farmers covered and total agricultural area insuredunder PMFBY and RWBCIS was negative (-1.04% & -4.86%) and positive (1.47% & 8.22%) respectively. TheAnalysis of variance (ANOVA) and Multiple Least Significant Difference (LSD) tests to compare the means offarmers’ premium, gross premium, claims reported, and claims paid showed a significant difference amongthe parameters under both the schemes. Multiple LSD results revealed a significant difference between farmers’premium and other parameters under both the schemes. Also,there was a significant difference between grosspremium and other parameters under PMFBY only denoting that the insurance companies were more benefitedunder the scheme.